2006
DOI: 10.2503/jjshs.75.312
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Changes in Transgenic Chrysanthemum morifolium Ramat. ‘Ogura-nishiki’ with rolC

Abstract: The effects of rolC on morphogenesis of Chrysanthemum morifolium Ramat. 'Ogura-nishiki' were studied. The ray flowerets in the rolC-transformed plants were shorter than those in wild-type plants, but the transformation enhanced outgrowth of lateral shoots and reduced internode elongation. Studies on adventitious shoot and root formation from leaf segments revealed that the rolC transgene led to reduced root formation but enhanced adventitious bud formation. This enhanced cytokinin-like activity was consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
1
5
0
1
Order By: Relevance
“…All transgenic plants produced flowers earlier but fewer in number compared to control plants. It has been reported that rolA and rolC genes are involved in gibberellins imbalance, either free or in conjugate form (Dehio et al 1993;Kubo et al 2006;Piispanen et al 2003). Such imbalance in gibberellins may be involved in the generation of the flowers before time but the dwarf canopy of transformed plants can result in the production of a lesser number of flowers.…”
Section: Resultsmentioning
confidence: 98%
“…All transgenic plants produced flowers earlier but fewer in number compared to control plants. It has been reported that rolA and rolC genes are involved in gibberellins imbalance, either free or in conjugate form (Dehio et al 1993;Kubo et al 2006;Piispanen et al 2003). Such imbalance in gibberellins may be involved in the generation of the flowers before time but the dwarf canopy of transformed plants can result in the production of a lesser number of flowers.…”
Section: Resultsmentioning
confidence: 98%
“…The identity of the fragments amplified ( Figure 1) by RT-PCR were confirmed by the analysis of the sequences obtained from purified and cloned fragments. Due to the fact that the sequences of all the genes amplified, uidA, aph3'II and act-cr, resulted in 100% identity with sequences reported in the data base of NCBI, it is quite feasible to use the records of transformed calluses based on this evidence, as has been done in other reports (Kubo et al, 2006).…”
Section: Main Factors Affecting Genetic Transformation Of Chrysanthemummentioning
confidence: 99%
“…2000년 이전에는 Agrobacterium에 의한 국화 형질전환 기술 개발 자체에 집중되어 왔으나 (Takatsu et al 1999;Mitiouchkina and Dolgov 2000), 최근에는 내병성 (Kim et al 2011b), 내충 성 (Kim et al 2011a), 무측지성 (Han et al 2007;Hur et al 2013; Khodakovskaya et al 2009), 웅성불임성 (Shinoyama et al 2012), 왜화성 (Kubo et al 2006), 조기개화성 (Han et al 2009;Khodakovskaya et al 2009;Lee et al 2012;Shulga et al 2011 질전환 5계통의 영양번식 제1세대(T0V1)에서의 무측지성 을 조사해 본 결과, LeLs80 1계통만이 무측지성이 유지되 는 것을 확인하였다 (Hur et al 2013 (Fig. 2), Northern 분 석을 실시한 결과, LeLs-antisense 유전자의 전사체 또한 정 상적으로 발현되는 것을 확인할 수 있었다 (Fig.…”
unclassified